Front vs Back and Barbell vs Machine Overhead Press: An Electromyographic Analysis and Implications For Resistance Training - Coratella, Giuseppe; Tornatore, Gianpaolo; Longo, Stefano; Esposito, Fabio; Cè, Emiliano (Frontiers in Physiology, 2022)
Overhead press is commonly performed to reinforce the muscles surrounding the shoulders. However, many overhead press variations can be executed, thus varying the stimuli to each muscle. Therefore, the current study compared the muscles excitation during overhead press performed with the barbell passing in front or behind the head or using a shoulder press machine. Eight competitive bodybuilders performed in random order front (front-BMP) or back barbell military press (back-BMP), and front (front-MSP) with neutral handgrip or back machine shoulder press (back-MSP). Normalized surface electromyographic root mean square (RMS) of anterior, medial and posterior deltoid, upper trapezius, pectoralis major and triceps brachii was recorded during both the ascending and descending phases. During the ascending phase, anterior deltoid showed greater RMS in back-BMP than back-MSP [ES: 1.42, (95% confidence interval 0.32/2.51)]. Medial deltoid showed greater RMS in back-BMP than front-BMP [ES: 3.68(2.07/5.29)], and back-MSP [ES: 7.51(4.73/10.29)]. Posterior deltoid showed greater RMS in back-BMP than front-BMP [ES: 9.00(5.73/12.27)]. Pectoralis major showed greater RMS in front-BMP than back-BMP [ES: 3.11(1.65 to 4.56)] and in front-MSP than back-MSP [ES: 20.52(13.34/27.70)]. During the descending phase, anterior deltoid was more excited in back-BMP compared to front-BMP [ES: 7.66(4.83/10.49). Medial deltoid showed greater RMS in back-BMP than front-BMP [ES: 4.56(2.70/6.42)]. Posterior deltoid showed greater RMS in back-BMP than front-BMP [ES: 8.65(5.50/11.80)]. Pectoralis major showed greater RMS in front-BMP than back-BMP [ES: 4.20(2.44/5.95)]. No between-exercise difference was observed for upper trapezius. Performing back overhead press enhances the excitation of medial and posterior and partly anterior deltoid, while front overhead favors pectoralis major. Overhead press performed using barbell excites muscles more than using machine to stabilize the trajectory of the external load. Different variations of overhead press appear to provide different stimuli to the shoulder muscles and may be used accordingly during the training routine.